Aberrant adhesion impacts early development in a Dictyostelium model for juvenile neuronal ceroid lipofuscinosis. Issue 4 (4th July 2017) - Huber, Robert J.; Myre, Michael A.; Cotman, Susan L.
ABSTRACT: Neuronal ceroid lipofuscinosis (NCL), also known as Batten disease, refers to a group of severe neurodegenerative disorders that primarily affect children. The most common subtype of the disease is caused by loss-of-function mutations in CLN3, which is conserved across model species from yeast to human. The precise function of the CLN3 protein is not known, which has made targeted therapy development challenging. In the social amoeba Dictyostelium discoideum, loss of Cln3 causes aberrant mid-to-late stage multicellular development. In this study, we show that Cln3-deficiency causes aberrant adhesion and aggregation during the early stages of Dictyostelium development. cln3 − cells form ∼30% more multicellular aggregates that are comparatively smaller than those formed by wild-type cells. Loss of Cln3 delays aggregation, but has no significant effect on cell speed or cAMP-mediated chemotaxis. The aberrant aggregation of cln3 − cells cannot be corrected by manually pulsing cells with cAMP. Moreover, there are no significant differences between wild-type and cln3 − cells in the expression of genes linked to cAMP chemotaxis (e.g., adenylyl cyclase, acaA; the cAMP receptor, carA; cAMP phosphodiesterase, pdsA; g-protein α 9 subunit, gpaI). However, during this time in development, cln3 − cells show reduced cell-substrate and cell-cell adhesion, which correlate with changes in the levels of the cell adhesion proteins CadA and CsaA. Specifically, loss of Cln3 decreases the intracellular level of CsaA and increases the amount of soluble CadA in conditioned media. Together, these results suggest that the aberrant aggregation of cln3 − cells is due to reduced adhesion during the early stages of development. Revealing the molecular basis underlying this phenotype may provide fresh new insight into CLN3 function.